SAT0048 The pattern of acpa reactivities in anti-ccp positive individuals with non-specific musculoskeletal symptoms at risk of developing ra. (15th June 2017) - Hensvold, A; Kisten, Y; Joshua, V; Hansson, M; Mathsson-Alm, L; Karlsson, A; Rezaei, H; Klint, E af; Fei, G; Catrina, A
Abstract : Background: There is today a paucity of prospective studies to describe the natural longitudinal history of anti-ccp positive individuals developing RA or not developing RA. Further no study to investigate the detailed ACPA reactivities in such a setting is currently available. Methods: Individuals at risk of developing RA were included in a cohort at Karolinska University Hospital, Stockholm. Examinations of peripheral joints was repeated at one year follow-up visit or at any time the patients experienced worsening of their symptoms. Peripheral blood samples were available at inclusion (n=70). Serum was run on a microarray based on the ImmuoCAP ISAC system testing for ACPA reactivities toward 13 different citrullinated peptides (fillagrin, fibrinogen, alpha-enolase, vimentin, histone) (1). Results: Individuals referred from primary care with musculoskeletal complaints and positive anti-ccp test were systematically investigated as part of routine care at our rheumatology clinic. Individuals lacking self-reported history of suspect arthritis, clinical arthritis according to rheumatologist and signs of synovitis on ultrasound examination were included in a clinical Risk-RA program with life-style coaching and personalized information on the risk of developing RA. Seventy individuals, with a mean age of 48 years (SD 15) and 86% females, were included in the program. Twenty (29%) individuals developed arthritis during a medium follow up time of 7 months (range 1–25 months). Number of ACPA reactivities at baseline was significant higher among those developing (in mean 6 reactivities) as compared to those not developing arthritis (in mean 4 reactivities). A increased proportion of individuals were showing reactivity towards citrullinated (cit) vimentin (vim) 60–75, fibrinogen (fib) 573 and enolase (eno) (CEP-1) among those developing arthritis (80% for anti-cit-vim 45% for anti-cit-fib and 60% for anti-cit eno) as compared to those not developing arthritis (41% for anti-cit-vim, 30% for anti-cit-fib and 52% for anti-cit-eno). Increased level of anti-cit-vim and anti-cit-eno antibodies was also observed at inclusion for those individuals developing arthritis as compared to those not developing arthritis. Conclusions: We describe here the pattern of ACPA reactivities in anti-CCP positive individuals with non-specific musculoskeletal symptoms at risk of developing RA and without clinical and ultrasonograph signs of synovitis and report that 30% of these patients will develop arthritis during a short follow-up. Number, frequency and titers of specific ACPA reactivities appear to be enriched already at inclusion among those patients that developed arthritis during follow-up. References: Hansson et al Arthritis Res Ther 2012. Disclosure of Interest: None declared